AKTIVITAS DAN MOTIVASI ANGGOTA DALAM TIM ESPORTS DI PEKANBARU - Wafi Hugman; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The development of technology is not only found in the industry, transportation, information and communication areas, but nowadays there are already many types of technologies developing in the entertainment sector. Game industry has entered Indonesia and it becomes attraction for some people, especially the youth who have good potential and ability in that sector. Not just playing for fun, lately young people are starting to compete and make a match in the world of electronic games or commonly called esports. In this study, the authors used a purposive technique and selected 5 informants who were joined into 4 different teams by using type of descriptive qualitative study. The existence of an esports competition surely makes them have various kinds of achievement motivation and goals such as becoming a professional player, gaining popularity and making money, so that they build a team in that sector which can be called an esports team. In the esports team, there is a reciprocal relationship between members, there are norms in the esports team, and it is a real unity so that in this study was found that members had various patterns of activities in them such as training activities, tournaments and other social activities within the group by the form of organic social solidarity that they applied in team games.Keywords:Esports Team, Social Solidarity, Achievement Motivation